2014
DOI: 10.1111/jpy.12253
|View full text |Cite
|
Sign up to set email alerts
|

Finding of 132, 173‐cyclopheophorbide a enol as a degradation product of chlorophyll in shrunk zooxanthellae of the coral Montipora digitata

Abstract: We examined the morphology and pigment composition of zooxanthellae in corals subjected to normal temperature (27°C) and thermal stress (32°C). We observed several normal and abnormal morphological types of zooxanthellar cells. Normal cells were intact and their chloroplasts were unbroken (healthy); abnormal cells were shrunken and had partially degraded or broken chloroplasts, or they were bleached and without chloroplasts. At 27°C, most healthy zooxanthellar cells were retained in the coral tissue, whereas s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 56 publications
(125 reference statements)
1
5
0
Order By: Relevance
“…The HPLC system was equipped with a ZORBAX Eclipse Plus C8 column (2.1 × 50 mm; Agilent Technologies, Santa Clara, CA, USA). Pigments were extracted using a combination (1:3) of dry sediment and acetone (90% final concentration; Alsterberg et al, 2011), sonicated for 15 min, and maintained overnight in the dark at −30 • C. Extracts were filtered using a syringe filter (0.2 µm, Millex-LG; Millipore, Bedford, MA, USA; Suzuki et al, 2015) and 1.0 mL of each extract was mixed with 0.2 mL of deionized water (Milli-Q water, Millipore) immediately before injections (Zapata et al, 2000) in the HPLC system. Separated pigments were detected spectrophotometrically using a photodiode array detector (SPD-M30AD; Shimadzu, Kyoto, Japan) with an optical resolution of 1.2 nm across the 320-720 nm bandwidth.…”
Section: Pigments and Benthic Microalgal Observationsmentioning
confidence: 99%
“…The HPLC system was equipped with a ZORBAX Eclipse Plus C8 column (2.1 × 50 mm; Agilent Technologies, Santa Clara, CA, USA). Pigments were extracted using a combination (1:3) of dry sediment and acetone (90% final concentration; Alsterberg et al, 2011), sonicated for 15 min, and maintained overnight in the dark at −30 • C. Extracts were filtered using a syringe filter (0.2 µm, Millex-LG; Millipore, Bedford, MA, USA; Suzuki et al, 2015) and 1.0 mL of each extract was mixed with 0.2 mL of deionized water (Milli-Q water, Millipore) immediately before injections (Zapata et al, 2000) in the HPLC system. Separated pigments were detected spectrophotometrically using a photodiode array detector (SPD-M30AD; Shimadzu, Kyoto, Japan) with an optical resolution of 1.2 nm across the 320-720 nm bandwidth.…”
Section: Pigments and Benthic Microalgal Observationsmentioning
confidence: 99%
“…Number in each star or diamond denotes the total number of species examined in the present study and/or previously reported (listed in Supplementary Table S2). Numbers with asterisks are data from previous reports [8, 1214]. Among the nine MEAs, Archaeplastida examined in the present study consists exclusively of phototrophs, whereas Amoebozoa and Opisthokonta consist exclusively of heterotrophs.…”
Section: Resultsmentioning
confidence: 60%
“…We also conducted experiments on 112 unialgal cultures (UCs), and accumulation of CPE was found to be common among algae containing secondary chloroplasts, including chlorarachniophytes, phototrophic dinoflagellates (dinophytes) [1214], haptophytes, and phototrophic euglenids (euglenophytes; Fig. 1, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations